STRATEGI BERTAHAN HIDUP DI TIGA WILAYAH - Dyah Ratih Sulistyastuti; Faturochman Faturochman (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2000)
The paradigm of trickle down effect development is not occurred by itself. Thus, there are some groups within the society that still have not derived from the outcome of the development. Those groups remain living in poverty which need government attention. Although the government has intervened to undertake poverty in the forms of the national development programs, have not been able to achieve their goals due to the various drawbacks and implementations. These obstructions have frequently related with the decision of the aspects of real target groups, and the problems of the unequal distribution. Besides problems of implementation, these programs had not meet with success in providing empowerment and sustainability, therefore, the poor had to actively create a strategy for survival. In discussing issues about poverty, it is imperative to further examine not only the causes and the problems of it, but also another important issue such as efforts of the suffering society to overcome its problem. Various strategies as a response of the limitations of government role towards society can be categorized into two levels: the households, that would be the focus of the discussion, and the community levels.